EFFECT OF CALCIUM FORTIFICATION ON HEALTH - Santosa, Winnie Nirmala (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2024)
Background: As a crucial micronutrient needed for numerous actions related to human health, calcium. Lack of calcium will have an effect on metabolism and body systems, so nutritional intervention in the form of calcium fortification is needed.Objective: To analyze the benefits of calcium fortification on improving health status. Methods: Using a literature review with a narrative method by searching Google Scholar and PubMed then extracting information from the relevant articles. Result: Calcium fortification can improve metabolism and body system work. Conclusion: The addition of calcium through the fortification process is proven to improve health.